Probing carbonate in bone forming minerals on the nanometre scale. (1st July 2015) - Kłosowski, Michał M.; Friederichs, Robert J.; Nichol, Robert; Antolin, Nikolas; Carzaniga, Raffaella; Windl, Wolfgang; Best, Serena M.; Shefelbine, Sandra J.; McComb, David W.; Porter, Alexandra E.
Graphical abstract: Abstract: To devise new strategies to treat bone disease in an ageing society, a more detailed characterisation of the process by which bone mineralises is needed. In vitro studies have suggested that carbonated mineral might be a precursor for deposition of bone apatite. Increased carbonate content in bone may also have significant implications in altering the mechanical properties, for example in diseased bone. However, information about the chemistry and coordination environment of bone mineral, and their spatial distribution within healthy and diseased tissues, is lacking. Spatially resolved analytical transmission electron microscopy is the only method available to probe this information at the length scale of the collagen fibrils in bone. In this study, scanning transmission electron microscopy combined with electron energy-loss spectroscopy (STEM-EELS) was used to differentiate between calcium-containing biominerals (hydroxyapatite, carbonated hydroxyapatite, beta-tricalcium phosphate and calcite). A carbon K-edge peak at 290 eV is a direct marker of the presence of carbonate. We found that the oxygen K-edge structure changed most significantly between minerals allowing discrimination between calcium phosphates and calcium carbonates. The presence of carbonate in carbonated HA (CHA) was confirmed by the formation of peak at 533 eV in the oxygen K-edge. These observations were confirmed by simulations using density functional theory. Finally, we show that this method can be utilised to map carbonate from the crystallites in bone. We propose that our calibration library of EELS spectra could be extended to provide spatially resolved information about the coordination environment within bioceramic implants to stimulate the development of structural biomaterials.